Association between sleep duration and chronic musculoskeletal pain in US adults: a cross-sectional study - Li, Chong; Huang, Huaping; Xia, Qingjie; Zhang, Li (Frontiers in Medicine, 2024)
Background: This study aims to explore the association between sleep duration and the prevalencerisk of developing chronic musculoskeletal pain (CMP).Methods: A cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2009-2010, which involved multiple centers across the United States. The study included 3,904 adults selected based on age and complete data availability. Demographic variables such as gender, age, race, and socioeconomic status (represented by the poverty-to-income ratio) were considered.Results: Of the participants, 1,595 reported less than 7 hours of sleep, 2,046 reported 7-8 hours, and 263 reported more than 9 hours of sleep. Short sleep duration was associated with a higher risk Odds of CMP (OR=1.611, 95% CI: 1.224-2.020, P=0.005). Long sleep duration also showed an higher prevalence (OR, 1.751; 95% CI, 0.923 to 3.321; P=0.059), although this result was not statistically significant.Long sleep duration also showed a trend towards increased risk (OR=1.751, 95% CI: 0.923-3.321, P=0.059), though less significant. A U-shaped relationship emerged (Effective degree of freedom (EDF) = 3.32, p < 0.001), indicating that 7 hours of sleep was associated with the lowest odds of CMP. In individuals with sleep durations less than 7 hours, each hour increment correlated with 22.8% reduced odds of CMP (OR, 0.772; 95% CI, 0.717-0.833; P=0.002). Beyond 7 hours, each hour increment was associated with 38.9% increased odds of CMP (OR, 1.389; 95% CI, 1.103-1.749; P=0.049).A U-shaped relationship emerged, indicating a lower risk of CMP with sleep duration ≤7 hours (OR=0.772, 95% CI: 0.717-0.833, P=0.002) and an elevated risk with sleep duration >7 hours (OR=1.389, 95% CI: 1.103-1.749, P=0.049).The findings suggest that both insufficient and excessive sleep durations are linked to an increased riskhigher prevalence of developing CMP, highlighting the importance of optimal sleep duration for musculoskeletal health.